Sulfonyl-based non-fullerene electron acceptor-assisted grain boundary passivation for efficient and stable perovskite solar cells. Issue 34 (14th August 2019) - Song, Changjian; Li, Xiaodong; Wang, Yueming; Fu, Sheng; Wan, Li; Liu, Shiyu; Zhang, Wenjun; Song, Weijie; Fang, Junfeng
Abstract : A sulfonyl-basedIDIS-Th passivated perovskite film for high-efficiency and high-stability perovskite solar cells. Abstract : Passivating the grain boundary (GB) defects of polycrystalline perovskite films via fused-ring non-fullerene Lewis base deactivators is an effective approach to fabricate high-efficiency and high-stability perovskite solar cells (PSCs). We first introduced the sulfonyl group (OSO) to substitute the carbonyl group (CO) group of fused-ring non-fullerene Lewis base deactivators. The novel acceptor material (IDIS-Th ) possessing the sulfonyl group exhibited stronger interactions with the under-coordinated Pb ions or Pb clusters in a perovskite film compared with the contrast (IDIC-Th ) to lower the trap density. Consequently, theIDIS-Th -containing PSC device achieved a higher-efficiency of over 20%, with a heightened V OC of 1.116 V, J SC of 22.67 mA cm −2 and FF of 79.1%. Moreover, the deactivators filling GBs could inhibit ion migration and resist moisture ingress, resulting in better environmental and thermal stabilities of PSC devices. Our results provide an alternative approach for designing and synthesizing better passivators to improve the performance of PSCs.